EFFECT OF SKIN EXTRACT MANGOSTEEN (GARCINIA MANGOSTANA L.) AGAINST SPERM QUALITY AND MALONDIALDEHYDE LEVELS OF MICE (MUS MUSCULUS) EXPOSURED WITH 2-METHOXYETHANOL - NATALIA DEBI SUBANI (JURNAL INFO KESEHATAN, 2014)
Levels of Reactive Oxygen Species a high negative impact on sperm quality and lead to increased levels of malondialdehyde. To overcome this use of mangosteen peel extract as an antioxidant. This study using mice exposed to the compound 2-Methohyethanol for 5 days and then treated with mangosteen peel extract at a dose of 25, 50 and 100 mg/kg for 35 in the sub cutaneous, while the control group only exposed to 2 - Methoxyethanol. Analysis of quality motility, morphology, viability, membrane integrity), and levels of malondialdehyde spermatozoa using sperm derived from the cauda epididymis. The results showed a dose of 25 mg/kg body weight more effectively improve the speed of motility, normal morphology and viability of spermatozoa that had been exposed to 2-Methoxyethanol, a dose of 50 mg/kg increased sperm membrane integrity and reduce levels of malondialdehyde, whereas a dose of 100 mg/kg body weight and reduce sperm quality increased levels of malondialdehyde. The conclusion is mangosteen rind extract improve sperm quality and reduce levels of malondialdehyde mice that had been exposed to 2-Methoxyethanol.